Modulating T Cell Responses via Autophagy: The Intrinsic Influence Controlling the Function of Both Antigen-Presenting Cells and T Cells - Merkley, Seth D.; Chock, Cameron J.; Yang, Xuexian O.; Harris, James; Castillo, Eliseo F. (Frontiers in Immunology, 2018)
Autophagy is a homeostatic and inducible process affecting multiple aspects of the immune system. This intrinsic cellular process is involved in MHC-antigen (Ag) presentation, inflammatory signaling, cytokine regulation and cellular metabolism. In the context of T cell responses, autophagy has an influential hand in dictating responses to self and non-self by controlling extrinsic factors (e.g. MHC-Ag, cytokine production) in antigen-presenting cells (APC) and intrinsic factors (e.g. cell signaling, survival, cytokine production and metabolism) in T cells. These attributes make autophagy an attractive therapeutic target to modulate T cell responses. In this review, we examine the impact autophagy has on T cell responses by modulating multiple aspects of APC function; the importance of autophagy in the activation, differentiation and homeostasis of T cells; and discuss how the modulation of autophagy could influence T cell responses.